Enhancing Readiness for Discharge through Effective Teaching: A Study on Low Birth Weight Mothers in NICU - Rara Angela; Riri Novayelinda; Ganis Indriati (LPPM Universitas Harapan Bangsa, 2024)
Maternal readiness for home care is crucial for optimal LBW outcomes. However, there are still many mothers who feel unprepared. The quality of discharge teaching provided to mothers is an important factor in this readiness. This study aims to determine the relationship between the quality of discharge teaching with discharge readiness in mothers of low birth weight (LBW) in the NICU. This study used a correlational method with a cross sectional approach. The study sample was 30 respondents based on inclusion and exclusion criteria using total sampling technique. Bivariate analysis with Fisher's exact test was used to analyze the data. Of the 30 respondents, 15 (50%) had a good level of discharge teaching quality, and 19 (63.3%) demonstrated good discharge readiness. The statistical test results demonstrated a significant relationship between the quality of discharge teaching and discharge readiness in mothers of low birth weight (LBW) in the NICU (p-value 0.016 < α 0.05). Mothers who received high-quality discharge teaching had a higher proportion of readiness for discharge (75%) compared to mothers who received low/moderate quality teaching (16.7%). The quality of discharge teaching plays an important role in improving discharge readiness in LBW mothers. Therefore, efforts to improve the quality of discharge teaching are recommended through effective communication training for nurses, and use of interactive learning media.